Macrophage cells secrete factors including LRP1 that orchestrate the rejuvenation of bone repair in mice. Issue 1 (December 2018) - Vi, Linda; Baht, Gurpreet; Soderblom, Erik; Whetstone, Heather; Wei, Qingxia; Furman, Bridgette; Puviindran, Vijitha; Nadesan, Puviindran; Foster, Matthew; Poon, Raymond; White, James; Yahara, Yasuhito; et al.
Abstract The pace of repair declines with age and, while exposure to a young circulation can rejuvenate fracture repair, the cell types and factors responsible for rejuvenation are unknown. Here we report that young macrophage cells produce factors that promote osteoblast differentiation of old bone marrow stromal cells. Heterochronic parabiosis exploiting young mice in which macrophages can be depleted and fractionated bone marrow transplantation experiments show that young macrophages rejuvenate fracture repair, and old macrophage cells slow healing in young mice. Proteomic analysis of the secretomes identify differential proteins secreted between old and young macrophages, such as low-density lipoprotein receptor-related protein 1 (Lrp1). Lrp1 is produced by young cells, and depletingLrp1 abrogates the ability to rejuvenate fracture repair, while treating old mice with recombinant Lrp1 improves fracture healing. Macrophages and proteins they secrete orchestrate the fracture repair process, and young cells produce proteins that rejuvenate fracture repair in mice. The rate of repair declines with age; however, exposure to young circulations can rejuvenate fracture repair, but how this is accomplished is unknown. Here, the authors identify proteins, including low-density lipoprotein receptor-related protein 1 (Lrp1), as being secreted from young macrophages and rejuvenating fracture repair in mice.